Molecular mechanism for the control of virulent Toxoplasma gondii infections in wild-derived mice - Murillo-León, Mateo (2020)
Some strains of the protozoan parasite Toxoplasma gondii (such as RH) are virulent in laboratory mice because they are not restricted by the Immunity-Related GTPase (IRG) resistance system in these mouse strains. In some wild-derived Eurasian mice (such as CIM) on the other hand, polymorphic IRG proteins inhibit the replication of such virulent T. gondii strains. Here we show that this resistance is due to direct binding of the IRG protein Irgb2-b1CIM to the T. gondii virulence effector ROP5 isoform B. The Irgb2-b1 interface of this interaction is highly polymorphic and under positive selection. South American T. gondii strains are virulent even in wild-derived Eurasian mice. We were able to demonstrate that this difference in virulence is due to polymorphic ROP5 isoforms that are not targeted by Irgb2-b1CIM, indicating co-adaptation of host cell resistance GTPases and T. gondii virulence effectors.